Eksistensi Minoritas Pendakwah Perempuan Peranakan Tionghoa di Indonesia: Studi Hj. Tan Mei Hwa - Farhan, Farhan; Romadlany, Zakiyah (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2024)
This article describes the existence of the role of Chinese Peranakan women who are active as preachers (da'iyah). Chinese Peranakan Muslims, although in a minority community group in Indonesia, have experienced significant development every year. The container for fostering the Chinese convert community in Indonesia has been built in the form of a hybrid worship, the mosque/prayer room building is built in the concept of a combination of Arab-Islamic (Nusantara) and Chinese (Peranakan) culture that resembles a 'klenteng' and has Nusantara characteristics. The Chinese Peranakan Muslim minority carries out Islamic studies through routine and intensive guidance for converts. Not a few Chinese Peranakan women appear to the public as preachers, for example Tan Mei Hwa in East Java. Through a study of media text analysis, virtual ethnographic studies and literature, this study concludes 4 findings: (1) Chinese Peranakan Women Preachers in Indonesia are still very minimal, but their existence is generally accepted by Muslims; (2) Chinese Muslim Women Preachers represent the role of women (Gender) in the public sphere who are not marginalized from the majority group; (3) As a Chinese descendant, female preachers demonstrate a moderate personal identity in religion and respect the diverse differences in tribe, ethnicity and race in the midst of social life in society, especially in Java; (4) female preachers receive equal recognition with other Chinese descendant preachers such as Ustadz Felix Siauw, Koko Liem, Koh Dennis Lim and others.